Prognosis and mortality risk in elderly patients with dengue virus infection: Excess fatality and the urgent need for revising current WHO criteria for elderly patients - Min-Jia Jeng; Nan-Yao Lee; Ing-Kit Lee; Yi-Chun Chen; Wen-Chi Huang; Jui-Chi Hsu; Chien-Hsiang Tai; Hao-Min Lan (Travel Medicine and Infectious Disease)
Background: The World Health Organization (WHO) reports a rising global incidence of dengue and severe outcomes among the elderly. This study investigates the differences in dengue characteristics between elderly and non-elderly patients and identifies mortality risk factors among elderly dengue patients. Methods: We conducted a retrospective study of adults (≥20 years) with dengue virus (DENV) infection at two medical centers from 2002 to 2018. Participants were divided into non-elderly (20–64 years) and elderly (≥65 years) groups. Results: A total of 1274 patients with laboratory-confirmed dengue were included in the study, of whom 373 (29.3 %) were classified as elderly. The majority of patients (67.5 %) were infected with DENV-2. In the overall cohort, age ≥65 years was identified as an independent predictor of mortality. Compared with non-elderly patients, elderly individuals exhibited significantly lower frequencies of classical dengue symptoms (e.g., fever, myalgia, bone pain, rash), but experienced higher rates of severe dengue, longer hospital stays, and more frequent complications, including acute kidney injury, severe hepatitis, bacteremia, pneumonia, and acute respiratory failure. The mortality rate was significantly higher among elderly patients (18 %) compared to non-elderly patients (2.7 %). Multivariate analysis among the elderly subgroup identified altered consciousness and pleural effusion at presentation, along with the development of acute kidney injury, severe hepatitis, and pneumonia during hospitalization, as independent predictors of mortality. Conclusions: The current WHO criteria may be insufficient for the timely identification of dengue in the elderly population. Excess mortality in this group underscores the urgent need for updated guidelines. Neurological symptoms, pleural effusion at presentation, and organ impairment during hospitalization are key predictors of mortality in elderly dengue patients.